2015
DOI: 10.3892/ol.2015.3120
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid inhibits migration, invasion and proliferation, and promotes apoptosis in glioma cells in vitro

Abstract: Abstract. All-trans retinoic acid (ATRA) is a derivative of vitamin A that can induce differentiation and apoptosis, as well as inhibit proliferation, in glioma cells. However, the effect of ATRA on the migration and invasiveness of glioma remains poorly understood. In addition, although it is universally accepted that ATRA can induce apoptosis and inhibit proliferation in glioma cells, the association between the concentration and effects of ATRA remain unclear. Therefore, the present study investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…As demonstrated in our work and others, ATRA causes differentiation of U87MG cells into fibrous astrocytes (Das et al, ; Karsy, Albert, Tobias, Murali, & Jhanwar‐Uniyal, ; Liang, Yang, & Guo, ; Shi et al, ). However, we demonstrated evidence of differentiation with ATRA released from a polymeric wafer rather than ATRA added to culture medium.…”
Section: Discussionsupporting
confidence: 81%
“…As demonstrated in our work and others, ATRA causes differentiation of U87MG cells into fibrous astrocytes (Das et al, ; Karsy, Albert, Tobias, Murali, & Jhanwar‐Uniyal, ; Liang, Yang, & Guo, ; Shi et al, ). However, we demonstrated evidence of differentiation with ATRA released from a polymeric wafer rather than ATRA added to culture medium.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies on the effect of ATRA on MMPs are overlapping and contradictory. While some studies show that ATRA upregulates MMPs 38 , others reported an opposite effect for ATRA in different cell types 39 40 41 . A possible explanation for this divergence is that ATRA exerts its effect by binding to different isoforms of the RARs, alpha, beta and gamma.…”
Section: Resultsmentioning
confidence: 99%
“…Due to different dosages, atRA can not only promote, but also inhibit, the proliferation of cells [18]. It has been reported that atRA treatment may inhibit the proliferation of glioma cells [19] and mouse embryonic palatal mesenchymal cells [16,17]. atRA-induced proliferation and survival has also been assessed in lung cancer cells [20,21], chicken primordial germ cells and neuronal cells [22].…”
Section: Discussionmentioning
confidence: 99%